Van der Westhuysen, J M. (Architect) Church Square Pretoria, Kruger Statue. Foot-piece. April 1941. Blueprints. - Van der Westhuysen, J M (My University, 2012)
Van der Westhuysen, J M. (Architect) Church Square Pretoria, Kruger Statue. Foot-piece. April 1941. Blueprints
Blueprints: Drawing no. 2: 745X430, Drawing no. 3: 745X410, and 665X510,
Keywords: Van der Westhuysen, J M. (Architect) Church Square Pretoria, Kruger Statue. Foot-piece. April 1941. Blueprints